PENGGUNAAN OLI BEKAS SEBAGAI BAHAN TAMBAH TERHADAP KARAKTERISTIK MARSHALL PADA DAUR ULANG OLI BEKAS - Yusrizal Lubis; Kartika Indah Sari (Jurnal Simetri Rekayasa, 2019)
Recycling methods can be used to reduce road construction costs. One of the recycling methods is mixing asphalt with used oil (lubricating oil), this method has been used by several AMP (Asphalt Mixing Plate) companies for asphalt mixtures. However, there is no reference / reference for the percentage of the oil mixture that is commonly used as an asphalt mixture. It is feared that an inappropriate oil mixture will cause damage or make the asphalt mixture not according to the specified specifications such as the stability and flow value of the asphalt mixture. The method used is an experiment, where 15 test objects are made using asphalt pen 60/70 to determine the KAO, after the KAO value is obtained, then used oil is mixed with variations of 1%, 2%, and 3%. From this research, the value of Stability and Flow in used oil mixtures with a variation of 1% Used oil obtained a stability value of 1033,936 kg and a flow of 3,21 mm, with the addition of 2% used oil, a stability value of 1037,246 kg and a flow of 3,25 were obtained. mm, the addition of 3% used oil obtained a stability value of 1040,142 kg and a flow of 3,30 mm. As the variation of the mixture of Stability and Flow values ​​increases, the percentage of addition of used oil mixture at 1%, 2%, 3%, Stability and flow values ​​meet the 2010 general specifications (revision 3), where the stability value has a minimum of 800 and the flow value a minimum of 2 and a maximum of 4. From the results of the marshall test of used oil mixtures, which start from a variation of 1% to 3% seen from the marshall parameters and data processing, the variation that is used as the optimum asphalt content in used oil added ingredients is the used oil variation of 3%.